Managerial Rents vs. Shareholder Value in Delegated Portfolio Management: The Case of Closed-End Funds - Wu, Youchang; Wermers, Russ; Zechner, Josef (Review of Financial Studies, 2016)
We examine the dynamics of assets under management (AUM) and management fees at the portfolio manager level in the closed-end fund industry. We find that managers capitalize on good past performance and favorable investor perceptions about future performance, as reflected in fund premiums, through AUM expansions and fee increases. However, the penalties for poor performance or unfavorable investor perceptions are either insignificant, or substantially mitigated by manager tenure. Long tenure is generally associated with poor performance and high discounts. Our findings suggest substantial managerial power in capturing CEF rents. We also document significant diseconomies of scale at the manager level. Received December 2, 2013; accepted June 21, 2016 by Editor Laura Starks.